2017
DOI: 10.1016/j.fgb.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Paracoccidioides spp. catalases and their role in antioxidant defense against host defense responses

Abstract: Dimorphic human pathogenic fungi interact with host effector cells resisting their microbicidal mechanisms. Yeast cells are able of surviving within the tough environment of the phagolysosome by expressing an antioxidant defense system that provides protection against host-derived reactive oxygen species (ROS). This includes the production of catalases (CATs). Here we identified and analyzed the role of CAT isoforms in Paracoccidioides, the etiological agent of paracoccidioidomycosis. Firstly, we found that on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 75 publications
(111 reference statements)
0
9
0
Order By: Relevance
“…Catalase and peroxidase catabolize H 2 O 2 . Paracoccidioides isolates encode three catalases, PbCatA, PbCatP , and PbCatB , which catalyze the decomposition of H 2 O 2 into oxygen and water (Chagas et al, 2008 ; Tamayo et al, 2017 ). CATP was up-regulated in all isolates of Paracoccidioides (Figure 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…Catalase and peroxidase catabolize H 2 O 2 . Paracoccidioides isolates encode three catalases, PbCatA, PbCatP , and PbCatB , which catalyze the decomposition of H 2 O 2 into oxygen and water (Chagas et al, 2008 ; Tamayo et al, 2017 ). CATP was up-regulated in all isolates of Paracoccidioides (Figure 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…Colony formation was monitored at 36 °C for 15–20 days. The phenotypic stability of the transformants was assessed by consecutive (at least three times) subculturing in BHI medium nonselective and then again in medium non-selective and selective medium with hygromycin B (150 μg mL −1 ) for three consecutive times at 36 °C 63,69 .…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Tamayo et al [ 156 ] recently identified and characterized the three members of the catalase (CAT) gene family in different fungal strains of Paracoccidioides spp., covering each phylogenetic lineage, as well as in other Onygenales. This study revealed that Coccidioides and dermatophyte genomes do not encode the extracellular catalase CATB, suggesting that Onygenales may have evolved different mechanisms to counteract oxidative stress via catalases.…”
Section: Defenses To Host Environment Stressorsmentioning
confidence: 99%